Factors associated with nursing students' adherence to venous blood collection practice guidelines – A cross sectional study. (March 2017) - Nilsson, Karin; Brulin, Christine; Grankvist, Kjell; Juthberg, Christina
Abstract: Venous blood specimen collection is a common procedure that nursing students perform during pre-registration courses, and training for such collections takes place on campus as well as at clinical placements. However, levels of adherence to practice guidelines are still suboptimal among both nursing students and healthcare staff. We aimed to explore nursing students' adherence to the Swedish national venous blood specimen collection practice guidelines regarding patient identification and test request management and how this adherence is related to clinical experience, capability beliefs, research use, and the perceived social climate in clinical contexts. A survey with a cross-sectional design was conducted among 305 nursing students at a medium-sized university in Sweden. Descriptive statistics and logistic regression were used for data analysis. The survey showed that 82% of the students adhered to patient identification guideline practices and 80% to test request management practices. Factors associated with correct patient identification procedures were semester and frequency of research use. Factors associated with correct test request management were previous healthcare work experience, semester, and capability beliefs regarding academic abilities and evidence-based practice. We conclude that there is a need to develop educational tools to train students in research use and evidence-based practice in order to enhance guideline practice adherence and improve patient safety. Highlights: Despite the use of venous sampling practice guidelines, adherence is suboptimal. Nursing students gradually deviate from guideline practice adherence. Clinical experience and capability beliefs are associated with guideline adherence. Social climate and research use are associated with guideline adherence. Actions must be taken to minimize the theory–practice gap.